Protein tyrosine phosphatase PTPN1 modulates cell growth and associates with poor outcome in human neuroblastoma - Caroline E. Nunes-Xavier; Olaia Aurtenetxe; Laura Zaldumbide; Ricardo López-Almaraz; Asier Erramuzpe; Jesús M. Cortés; José I. López; Rafael Pulido (BMC, 2019)
Abstract Background Protein tyrosine phosphatases (PTPs) regulate neuronal differentiation and survival, but their expression patterns and functions in human neuroblastoma (NB) are scarcely known. Here, we have investigated the function and expression of the non-receptor PTPN1 on human NB cell lines and human NB tumor samples. Material/methods NB tumor samples from 44 patients were analysed by immunohistochemistry using specific antibodies against PTPN1, PTPRH, PTPRZ1, and PTEN. PTPN1 knock-down, cell proliferation and tyrosine phosphorylation analyses, and RT-qPCR mRNA expression was assessed on SH-SY5Y, SMS-KCNR, and IMR-32 human NB cell lines. Results Knock-down of PTPN1 in SH-SY5Y NB cells resulted in increased tyrosine phosphorylation and cell proliferation. Retinoic acid-mediated differentiation of NB cell lines did not affect PTPN1 mRNA expression, as compared with other PTPs. Importantly, PTPN1 displayed high expression on NB tumors in association with metastasis and poor prognosis. Conclusions Our results identify PTPN1 as a candidate regulator of NB cell growth and a potential NB prognostic biomarker.